Viscosity Variation and Thermal Effects in Finite Journal Bearings - M. Ganapathi; S. Vijayakumar Varma; K. R. K. Prasad; V. Bharath Kumar (International Journal of Mathematics And its Applications, 2017)
In this paper In Finite Journal bearing considering the effects of additives in lubrication with viscosity variation and thermal effects are analyzed. The generalized Reynolds equation for two layer fluid is derived and is applied for finite journal bearing. The finite journal bearing with modified Reynolds equation is solved numerically by using Finite Difference Method technique. As the thermal effect increases for two layer fluids increases the pressure and load capacity in the lubrication process.